A comparative study on the effects of the ω and α phases on the temperature dependence of shape memory behavior of a Ti–27Nb alloy. (1st July 2015) - Al-Zain, Yazan; Kim, Hee Young; Koyano, Tamotsu; Hosoda, Hideki; Miyazaki, Shuichi
Abstract : While the stress for inducing the martensitic transformation in a Ti–27Nb alloy changed only slightly on aging, the stress at which the martensite phase starts to plastically deform and the ultimate tensile strength increased on aging due to the formation of thermal ω phase or α phase. An anomalous temperature dependence of the shape memory behavior was also observed and explained by the fact that the thermal ω phase encouraged the formation of the athermal ω phase during cooling.